Principles of electrical measurement - Tumanski, Sawomir (Series in sensors, 2006)
The field of electrical measurement continues to grow, with new techniques developed each year. From the basic thermocouple to cutting-edge virtual instrumentation, it is also becoming an increasingly "digital" endeavor. Books that attempt to capture the state-of-the-art in electrical measurement are quickly outdated. Recognizing the need for a text devoted to the major areas underlying modern electrical measurement, Slawomir Tumanski developed Principles of Electrical Measurement.